ITECSOL: EXTENSÃO QUE MATERIALIZA RESPONSABILIDADE SOCIAL DA UNIVERSIDADE - Barcelos, Eronita S.; Rasia, Pedro C.; Silva, Jorge A. d.; Basso, Lauri; Ferrari, Luciene; Villarreal, Jorge E. E.; Lassen, Manoel F. M. (Salão do Conhecimento, 2013)
Resumo